Promosi Kesehatan tentang Tumbuh Kembang Balita di Taman Posyandu Jeruk Desa Darungan Kecamatan Pare - wahyu wijayati; Eka Sri Purwandari (STIKES dan AKZI Karya Husada Kediri, 2022)
Toddler period as a golden period, window of opportunity, critical period which lasts very short and is sensitive and cannot be repeated again in the first five years of life, needs attention so that toddler growth and development can take place optimally. One of the health promotion efforts related to optimizing the growth and development of toddlers can be through health education about the growth and development of toddlers, among others, to mothers of toddlers at the Jeruk Posyandu Park, Darungan Village, Pare District, Kediri Regency, East Java Province; face-to-face, to provide health education to mothers of toddlers, namely about: definition of growth and development, growth and development period, growth and development factors, growth and development stages. Auxiliary media used in health education are laptops, LCDs, and leaflets. The timing of the implementation of health promotion activities regarding the growth and development of children under five at the Jeruk Posyandu Park, Darungan Village, Pare District, Kediri Regency, East Java Province, from March 12 to April 12 2022 with 24 mothers under five participating. The results of the activity evaluation showed an increase in the knowledge of mothers of children under five before and after the provision of health education and all mothers of children under five were very enthusiastic about participating in health education as indicated by the activity of all mothers of children under five in the question and answer session; so that it can be said that health promotion activities through health education about the growth and development of toddlers can be effective in increasing the knowledge of mothers of toddlers at the Jeruk Posyandu Park, Darungan Village, Pare District, Kediri Regency, East Java Province.